Desarrollo del proceso de regularización ambiental de los talleres del Gad municipal del cantón Latacunga, establecimiento del plan de manejo ambiental, para la minimización de impactos ambientales. - Alvaréz Garzón, Cristian Augusto (2017)
The GAD municipal of the canton Latacunga has and objective of mitigating the negative environmental impacts has mechanical workshops that focus their work on performing preventive services in the automotive employers of the Entity, dealing with activities such as oil changes, filters and lubricants, revision in general automotive, changes of accessories and bands. In this process, these aspects require mostly the use of chemical products that affect the environment and generate a significant impact on the use of soil, water and air; therefore, it is necessary that the Institution in coordination with each of the officials of the Municipal Workshop have the commitment to carry out their work without polluted agents. The workers training programs, surveillance, process evaluation and compliance with environmental regulations are used. Due to the precedent noted, the objective is to carry out the design and execution of an Environmental Management Plan, in order to improve the quality of the workshops' surroundings and, in turn, protect the patrimony belonging to the Institution.The methodology used is directed to the use of tools that allow to know the current state of the problem and through the use of tools applying communication plans for effective teamwork, in addition using a contingency plan, methods of waste management, as well as monitoring and control to techniques, prevention and mitigation of impacts, community relations, safety, as well as occupational health.